Renewable build-up pathways for the US: Generation costs are not system costs. (1st March 2015) - Becker, Sarah; Frew, Bethany A.; Andresen, Gorm B.; Jacobson, Mark Z.; Schramm, Stefan; Greiner, Martin
Abstract: The transition to a future electricity system based primarily on wind and solar PV is examined for all regions in the contiguous US. We present optimized pathways for the build-up of wind and solar power for least backup energy needs as well as for least cost obtained with a simplified, lightweight model based on long-term high resolution weather-determined generation data. In the absence of storage, the pathway which achieves the best match of generation and load, thus resulting in the least backup energy requirements, generally favors a combination of both technologies, with a wind/solar PV (photovoltaics) energy mix of about 80/20 in a fully renewable scenario. The least cost development is seen to start with 100% of the technology with the lowest average generation costs first, but with increasing renewable installations, economically unfavorable excess generation pushes it toward the minimal backup pathway. Surplus generation and the entailed costs can be reduced significantly by combining wind and solar power, and/or absorbing excess generation, for example with storage or transmission, or by coupling the electricity system to other energy sectors. Highlights: Start point: Hi-res weather-based wind and solar generation timeseries for the US. Renewable build-up pathways minimizing either backup energy or costs compared. Backup-minimal paths contain ∼80% wind, more sensitive to mix at higher penetrations. Minimal cost paths shift from least generation costs to least backup during build-up.